Art has a Place: Country as a teacher in the city. Issue 13 (9th November 2016) - Harrison, Neil; Page, Susan; Tobin, Leanne
Abstract: Country constitutes the very anchor of life for many Aboriginal and Torres Strait Islander people in Australia. It is central to Indigenous identities and history, and is a powerful signifier of overall health and well-being; yet, the significance of country to Indigenous people living in large urban localities such as Sydney, Australia, remains an enigma. Through the production of a series of three murals on a university campus, this project was designed to explore the significance of country for three Darug artists working alongside 90 pre-service teachers enrolled in teacher education. The authors were working with the notion that Aboriginal art comes from country and should stay on country; hence, the painting was directed by Darug artists because we were teaching and learning on Darug country. Our objective, though, was to explore through practice how country teaches in the city, and to produce new stories of coexistence. Narratives developed around terms of engagement and the relationships that developed through project partnerships.